Developing Interactive PowerPoint for Teaching Vocabulary in Higher Education - Retnita Saputri; Indah Tri Purwanti; Atni Prawati (Universitas Islam Negeri Palopo, 2025)
This research focuses on developing interactive PowerPoint materials using the ADDIE model of development. Employing the Research and Development (R&D) method, the research involved first-semester students from the English Study Program at Universitas Riau, Pekanbaru, who were enrolled in a Vocabulary course. Data were collected through a needs analysis questionnaire and expert judgment validation. A total of 38 students participated in the needs analysis. Expert validation was administrated from three domains: media, material, and pedagogy. The findings showed a preference for interactive PowerPoint as a learning media. The media validation results revealed “highly valid” scores: 85.5% for the